Fracture of pearlitic ductile cast iron under different loading conditions - Fernandino, Diego Omar (2014)
In this study, fracture surfaces of pearlitic ductile iron generated under impact, bending and fatigue tests were characterized and compared. The fracture mechanisms in each case were identified from the observation of SEM images and the characteristic topographic features were quantitatively and qualitatively evaluated. Cleavage was the predominant fracture mechanism for impact loading at all test temperatures and also for slow bending testing. On the other hand, under fatigue loading, the fracture surfaces showed a mix of cleavage and ductile striation areas. A complex but reliable methodology for the determination of the direction of propagation of the main crack was also proposed, based on a careful analysis of the river patterns along the cleavage planes.